2020
DOI: 10.1108/josm-05-2020-0145
|View full text |Cite
|
Sign up to set email alerts
|

Robotic transformative service research: deploying social robots for consumer well-being during COVID-19 and beyond

Abstract: PurposeBesides the direct physical health consequences, through social isolation COVID-19 affects a considerably larger share of consumers with deleterious effects for their psychological well-being. Two vulnerable consumer groups are particularly affected: older adults and children. The purpose of the underlying paper is to take a transformative research perspective on how social robots can be deployed for advancing the well-being of these vulnerable consumers and to spur robotic transformative service resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 90 publications
(140 reference statements)
2
97
0
2
Order By: Relevance
“…Implementation and contactless interaction during the pandemic will be more successful if the robot recognizes and adapts to the specific needs of the user. Personalization, which can include volume and speed control for the robot's voice, text size presented on displays, and the level of difficulty of an activity, can be especially important when there are multiple users for each robot [91].…”
Section: Personalizationmentioning
confidence: 99%
“…Implementation and contactless interaction during the pandemic will be more successful if the robot recognizes and adapts to the specific needs of the user. Personalization, which can include volume and speed control for the robot's voice, text size presented on displays, and the level of difficulty of an activity, can be especially important when there are multiple users for each robot [91].…”
Section: Personalizationmentioning
confidence: 99%
“…Well-being is central to studies in transformative service research (TSR) ( Barnes et al, 2020;Mollenkopf et al, 2020), as TSR is defined as "the integration of consumer and service research that centers on creating uplifting changes and improvements in the well-being of consumer entities: individuals (consumers and employees), communities and the ecosystem" (Anderson et al, 2011, p. 3). The COVID-19 pandemic has put increasing pressure on fundamental forms of well-being that result from social distancing (Henkel et al, 2020). Therefore, the underlying study offers a contribution to TSR, by focusing on loneliness as an indicator of well-being.…”
mentioning
confidence: 99%
“…It was suggested that after the crisis the whole system may not return to a previous condition, as parts of the system are likely to have changed irrevocably. The challenges may arise, such as finding ways to maintain the "human touch" of the service and finding new balance with automation (Rivera, 2020); deployment of companion robots to mitigate guests' frustration and feeling of loneliness and isolations for quarantine time (Henkel et al, 2020). Health-oriented tourism and wellness and spa hotel might be of the customer preferences after the end of the pandemic due to their slow tourism nature and comforting ambience (Wen et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%